PENGARUH KETIDAKPASTIAN TUGAS DAN DESENTRALISASI TERHADAP KINERJA MANAJERIAL DENGAN SISTEM AKUNTANSI MANAJEMEN SEBAGAI VARIABEL INTERVENING (Studi Pada PT. Gunanusa Utama Fabricators) - Yazid, Helmi (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2012)
This study aims to demonstrate the effect of decentralization on SAM, the SAM taskuncertainty, task uncertainty on managerial performance, the SAM on managerialperformance, decentralization on managerial performance, decentralization on managerialperformance, moderated by SAM, the uncertainty on the performance of managerial tasks tobe mediated by SAM. The research was conducted at PT. Gunanusa Main Fabricators inBojonegara-Serang. Respondents were selected as samples are middle managers and lower,amounting to 90 managers in PT. Gunanusa Main Fabricators in Bojonegara - Serang.Sampling technique in this study is a purposive sample withdrawal. Research resultsconcluded that the uncertainty of the task significant positive effect on managerialperformance. Employee Performance in PT. Main Fabricators Bojonegara Gunanusa Attacksignificant positive effect on Managerial Performance, Task Uncertainty significant positiveeffect on Management Accounting Systems, Decentralization significant positive effect onSystems Management Accounting, Management Accounting System significant positiveeffect on managerial performance, test results proved the indirect influence of the TaskUncertainty Managerial performance mediated by the Management Accounting System.Keywords : Task uncertainty, decentralization, system management accounting, managerialperformance